Spectrophotometry of H II regions in the spiral galaxy M101 - Sedwick, K. E. (1981)
Spectral line intensity data are presented for ionized hydrogen regions in the giant spiral galaxy M101. The influence of interstellar extinction is assessed and electron temperatures of the gas clouds are derived.